2000
DOI: 10.1039/a905433b
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Ti(iv)-doped α-FeOOH particles

Abstract: The in¯uence of Ti(IV) on the formation and structure of a-FeOOH particles was investigated by characterizing the coprecipitation products of Fe(III) with Ti(IV) at different atomic ratios (Ti/Fe) in the range 0±0.1. The particle width of the products increased as Ti/Fe was increased. At Ti/Fe¢0.05 the crystallite size of a-FeOOH increased with increase of Ti/Fe while the XRD peaks decreased in intensity. Thermal analysis and Mo È ssbauer spectroscopy showed that the a-FeOOH phase diminishes upon doping with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Heterogeneity in particle size as shown in SEM images, as well as lattice distortions and defects have been cited as the cause of the multiple peaks (Ishikawa et al 2000).…”
Section: Resultsmentioning
confidence: 98%
“…Heterogeneity in particle size as shown in SEM images, as well as lattice distortions and defects have been cited as the cause of the multiple peaks (Ishikawa et al 2000).…”
Section: Resultsmentioning
confidence: 98%
“…It means that Ti atoms placed even at below the interface are in the tetravalent state. Previous studies on structural analysis of FeOOH particle, which is corrosion product of steel, precipitated from aqueous solution containing Ti 4+ suggested that Ti 4+ promotes the formation of α-FeOOH fine particles and inhibits the formation of unstable β-FeOOH [5,6]. It may produce similar effects on stainless steel surface.…”
Section: -2 Angle Resolved Hx-pesmentioning
confidence: 90%
“…Cr oxide film plays a role as the protective film to interrupt a progression of rust formation into the bulk. The small amount of additional elements such as Ti, Nb, Cu, Ni and so on are known to improve corrosion resistance property of passivation film [5,6]. It is not, however, precisely known how such elements play a role in improvement of corrosion resistance yet.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Al and Ti ions can substitute on the Fe site. [35][36][37] From these results, it is found that the initial state, e.g., pre-existing cracks, and impurities model corresponding to the goethite in Fig. 6(a).…”
Section: Tem Observation Of Pore Morphologymentioning
confidence: 91%
“…Numerous articles related to study of the goethite-hematite phase transformation by thermogravimetric analysis, [21][22][23][24][25][26] pore morphology observation, 22,[27][28][29][30][31][32] crystal structure analysis, 22,23,29,[31][32][33][34] and using substitutional elements such as Al and Ti [35][36][37] have been published. When goethite transforms to hematite by thermal decomposition at lower temperature (below 300°C), uniform slit-shaped micropores are formed in the hematite.…”
Section: Introductionmentioning
confidence: 99%